SCREENING FOR EXERCISE HABITS IN ADOLESCENTS AT SMPN 13 MAKASSAR CITY - Ganing, Anwar; Rezki Anisa, Nurul; A. Sabil, Fitri; Abrar, Eva Arna; Fauzia, Liza (INCIDENTAL : Journal Of Community Service and Empowerment, 2024)
The purpose of this community service activity is to identify and evaluate exercise habits in adolescents through screening with a questionnaire, as well as the factors that influence them. Exercise has an important role in supporting the physical and mental development of adolescents, but the level of participation in physical activity in this age group tends to decrease. Screening of exercise habits was carried out using a questionnaire that included the frequency, duration, type, and intensity of exercise performed by adolescents. In addition, factors considered included motivation, social support, access to sports facilities, and perceptions of the importance of exercise. The screening results showed that most adolescents did not meet the physical activity recommendations recommended by the World Health Organization, with factors such as lack of free time, interest in other activities, and limited facilities being the main obstacles. This study also found differences in exercise habits based on gender, age, and socioeconomic status. These findings highlight the importance of developing intervention programs that can increase exercise participation among adolescents, as well as the need for greater support from families, schools, and communities to create an environment that supports healthy living habits